What is meant by "rigour" in evidence-based educational policy and what's so good about it?. Issue 1 (17th February 2019) - Cartwright, Nancy
ABSTRACT: Across the evidence-based policy and practice (EBPP) community, including education, randomised controlled trials (RCTS) rank as the most "rigorous" evidence for causal conclusions. This paper argues that that is misleading. Only narrow conclusions about study populations can be warranted with the kind of "rigour" that RCTs excel at. Educators need a great deal more information to predict if a programme will work for their pupils. It is unlikely that that information can be obtained with EBPP-style rigour. So, educators should not be overly optimistic about success with programmes that have been "rigorously" tested. I close with a plea to the EBPP community to take on the job of identifying and vetting the information educators need in practice.